2021
DOI: 10.1111/jiec.13179
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of material inflows to in‐use stocks in 2011 and its implications for a circularity transition

Abstract: Around 40% of global raw materials that are extracted every year accumulate as in-use stocks in the form of buildings, infrastructure, transport equipment, and other durable goods. Material inflows to in-use stocks are a key component in the circularity transition, since the reintegration of those materials back into the economy, at the end of the stock's life cycle, means that less extraction of raw materials is required. Thus, understanding the geographical, material, and sectoral distribution of material in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
1
2
0
2
Order By: Relevance
“…To a great extent, this could be due to the continued expansion of in-use stocks. In fact, recent studies estimate that up to 40% of global raw materials mined each year accumulate as in-use stocks, e.g., buildings, infrastructures, means of transport (Aguilar-Hernandez et al, 2021). Similar findings were also highlighted in Europe.…”
Section: Discussionsupporting
confidence: 65%
“…To a great extent, this could be due to the continued expansion of in-use stocks. In fact, recent studies estimate that up to 40% of global raw materials mined each year accumulate as in-use stocks, e.g., buildings, infrastructures, means of transport (Aguilar-Hernandez et al, 2021). Similar findings were also highlighted in Europe.…”
Section: Discussionsupporting
confidence: 65%
“…2 We also identified one study that uses the physical-monetary hybrid unit input-output database EXIOBASE v3.3 instead of its purely monetary version to allocate an extension of material gross additions to stock (GAS) to industry and final demand sectors (Aguilar-Hernandez et al, 2021). The extension was constructed via mass-balancing resource use and waste accounts (Merciai & Schmidt, 2018).…”
Section: Low End-use Resolutionmentioning
confidence: 99%
“…Building on this, we reviewed previous studies and found consistent outcomes (Table S4). One aspect not factored in is the effect of yield: the volume of materials retained in the product during its production.…”
Section: Discussionmentioning
confidence: 65%